Pengembangan Aplikasi Navigasi Berbasis Android : Kalkulasi Back Azimuth dan Deteksi Deviasi Secara Realtime - Axel, Rafael; Naury, Chairullah; Pantjarani, Ari (Politeknik Harapan Bangsa Surakarta, 2024)
Navigation plays a crucial role in daily life, supporting human activities to explore the environment effectively. In the military field, navigation involves understanding terrain science, map orientation, resection, intersection, azimuth, back-azimuth, distance measurement, elevation, compass, and topographic map interpretation. These skills make navigation critical in defense and tactical operations, requiring high precision and quick mobility in dynamic combat environments. The use of traditional tools has proven inefficient in unfamiliar and complex terrains, thus necessitating a mobile and practical navigation application. The author designed an Android-based application focused on calculating back-azimuth and detecting user deviation in real-time. The methodology used is Rapid Application Development (RAD), involving planning, workshop design, and implementation stages. Through repeated collaboration with users, the application's requirements and design are refined to ensure alignment with user needs and organizational goals.